Study, Design, Fabrication and Testing of Perforated Pipes for Desilting Basin - Bhattarai, Aayush; Karna, Swekshya; Pandey, Samrat; Khadka, Anuragh (International Journal on Engineering Technology, 2025)
A desilting basin is a critical component of hydropower systems designed to remove sediment from the water flow before it enters the turbines. Over time, sedimentation can lead to various problems, including reduced water storage capacity followed by decreased turbine efficiency. The project focuses on the utilization of perforated pipes within desilting basins to address the sedimentation challenges. By tracing the historical evolution and diverse applications of perforated pipes in sediment control, the study explores their potential as a cost-effective and efficient solution for enhancing sediment removal in desilting basins. The theoretical framework, rooted in fluid mechanics, guides the design considerations, emphasizing factors such as flow distribution, velocity, perforation size and spacing. The objectives include designing and testing a functional perforated pipe system to visualize its effectiveness in maintaining optimal hydropower plant operations. While acknowledging limitations such as potential inefficiency for larger particles, it showcases promising results with a commendable 65% sediment removal efficiency in practical demonstrations, underscoring the viability of perforated pipes as a valuable tool in sediment control for sustainable hydropower systems.